2022
DOI: 10.3892/etm.2022.11484
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological profiles and therapeutic applications of pachymic acid (Review)

Abstract: This work is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International (CC BY-NC-ND 4.0) License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Pachymic acid is a bioactive ingredient of Poria cocos with various pharmacological properties, including anti-tumor, anti-inflammatory, antioxidant, hypoglycemic, and sedative hypnosis. 169 Furthermore, pachymic acid possesses beneficial effects against fibrosis. Li et al reported that pachymic acid alleviated rat pancreatic injury and fibrosis with pancreatitis, and the inhibition of NLRP3 inflammasome is involved.…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…Pachymic acid is a bioactive ingredient of Poria cocos with various pharmacological properties, including anti-tumor, anti-inflammatory, antioxidant, hypoglycemic, and sedative hypnosis. 169 Furthermore, pachymic acid possesses beneficial effects against fibrosis. Li et al reported that pachymic acid alleviated rat pancreatic injury and fibrosis with pancreatitis, and the inhibition of NLRP3 inflammasome is involved.…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…It is well-known that Poria cocos is composed of a number of essential components, including Pachymic acid (C 33 H 52 O 5 ), Pinylic acid (C 30 H 18 O 3 ), Songnyeongsinic acid (3--Hyderoxy-lanosta-7.9 (11), 24-Trien-21-oic acid, and Tumulosic acid (C 31 H 5 ). [5] Additionally, poricoic acid and phosphoric acid (Cortoic acid (C 51 ) are also derived from this source. The substance in question comprises perishaminoic acid, abricoic acid, polypothenic acid A and C, triterpenoid, ergosterol, lecithin, adenine, choline, glucose, fructose, protein, and a significant quantity of inorganic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PA also showed significant anticancer activities in animal models [ 19 21 ] by inhibiting the growth of NCI‑H23, SGC‑7901, and MIA PaCa‑2 xenograft tumors. In a review of the pharmacological profiles and therapeutic applications of PA, we systematically summarized the anticancer potential of PA and its underlying molecular mechanisms in vitro and in vivo [ 22 ]. However, to date, there is limited knowledge regarding the modification on the structure of PA to improve its anticancer activity [ 23 ].…”
Section: Introductionmentioning
confidence: 99%